2017
DOI: 10.4081/cp.2017.912
|View full text |Cite
|
Sign up to set email alerts
|

Combination Iron Chelation Therapy with Deferiprone and Deferasirox in Iron-Overloaded Patients with Transfusiondependent β-thalassemia Major

Abstract: There are few papers on the combination therapy of deferiprone (DFP) and deferasirox (DFX) in iron-overloaded patients with transfusion-dependent β-thalassemia major (β-TM). A total of 6 patients with β-TM (5 males and 1 female) with a mean age of 23.8±5.8 years (ranging from 17 to 31) used this treatment regimen. The mean doses of DFP and DFX were 53.9±22.2 and 29.3±6.8 mg/kg/day, respectively. The duration of treatment was 11.5±4.6 months. Their serum ferritin levels were measured to be 2800±1900 and 3400±16… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
3

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 11 publications
0
21
0
3
Order By: Relevance
“…MRI indexes have been used as one of the most important indicators for evaluating the iron burden in β‐TM patients (Voskaridou et al, ). The MRI‐based method for determining the LIC is a highly sensitive and specific method that reflects body iron store (Karami, Kosaryan, Amree, Darvishi‐Khezri, & Mousavi, ). Studies revealed that there is stronger correlation between LIC and body iron loading in patients with β‐TM (Voskaridou et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…MRI indexes have been used as one of the most important indicators for evaluating the iron burden in β‐TM patients (Voskaridou et al, ). The MRI‐based method for determining the LIC is a highly sensitive and specific method that reflects body iron store (Karami, Kosaryan, Amree, Darvishi‐Khezri, & Mousavi, ). Studies revealed that there is stronger correlation between LIC and body iron loading in patients with β‐TM (Voskaridou et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…During the case enrollment process, patient files were reviewed to obtain data on the following: lumbar spine and femoral neck z -scores at annual BMD measurements, age, gender, dependent/not dependent on blood transfusions, duration of blood transfusion(s), units of transfused blood per year, received iron via blood transfusion, iron-chelating therapy data, mean serum ferritin and hemoglobin (measured during the previous five years), mean ca (mg/dL) and vitamin D (ng/mL) levels during treatment with zoledronic acid, history of splenectomy, and history of diabetes mellitus. Each PRBC (packed red blood cell) packed contains 250 mg of iron; so, the iron intake from blood transfusions in mg/year was calculated as: 250 × the number of units given during one year ( 21 ). All patients were on a steady dose of iron-chelators during treatment with zoledronic acid [desferrioxamine (20-40 mg/kg/day), deferasirox (20-40 mg/kg/day), and deferiprone (50-100 mg/kg /day)].…”
Section: Methodsmentioning
confidence: 99%
“…Karami et al reported results of combining DFP (mean dose of 53.9±22.2 mg/kg/d) with DFX (mean dose of 29.3±6.8 mg/kg/d) in 6 patients with TDT after failing monotherapy, and showed non-significant increases in SF with a significant effect on LIC (change by 7.59±3.16 mg/g dw). 67 Furthermore, 33 patients with TDT who failed monotherapy were evaluated in a prospective study at a single center in India, with 12 patients continuing the 2-year treatment with 75 to 100 mg/kg/d DFP (divided into three doses) and 20 to 40 mg/kg/d DFX. 68 This regimen showed a reduction in the mean SF by 44.67%±13.78% at two years and was well tolerated with GI disturbances noted in around 6% of patients, and elevations in creatinine >33% above the baseline on two consecutive occasions noted in around 85% of patients.…”
Section: Dfp and Dfxmentioning
confidence: 99%